Development and Validation of the Mental Health Seeking Apprehension Scale (MHSAS) - Knowles, Simon Robert; Apputhurai, Pragalathan (Journal of Psychology and Psychotherapy Research, 2018)
As many as 1 in 5 individuals currently experience mental health issues, and that only a minority seek help from mental health professionals. This paper outlines the development and validation of the Mental Health Seeking Apprehension Scale (MHSAS). MHSAS was validated across three studies using both university and community samples. In the first study, exploratory factor analysis revealed a nine-item two-factor scale (N=231), which was confirmed in the second study (N=208). The first factor related to mental health stigma (e.g., embarrassed about help-seeking, not wanting others to know) while the second was related to ambivalence toward seeking help (e.g., nothing changes problems, professional may not be helpful). Based on a combination of Study 1 and 2 datasets, the third study (N=439) analysed MHSAS and help-seeking behaviour. Results suggest that greater perceived stigma and ambivalence were associated with not seeking mental health support and also greater psychological distress. The research provides good preliminary evidence that the MHSAS is a brief psychometrically valid measure of mental health help seeking apprehension. MHSAS can be utilised by health professionals and researchers to screen for apprehension relating to seeking mental health support and identify potential barriers preventing utilisation of mental health services when needed.